Character Building in Contemporary Islamic Education and the Impact of Rauá¸ah Al Aá¹fal Teacher Character Values Implementation in Rauá¸ah Al Aá¹fal (RA) Muslimat Nahdlatul Ulamaâ€™ (NU) 1 Dinoyo Malang City - Sudirman Sudirman; Hayat Hayat (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The aim of this research is to gain a holistic understanding of: First, what are the impacts of the RA teachersâ€™ character values implementation in RA Muslimat NU 1 Dinoyo, Malang City. Second, how to build RA teachersâ€™ character in RA Muslimat NU 1 Dinoyo, Malang City in Contemporary Islamic education. Based on the desired objective, this is a case study using qualitative approach, that points out the importance of building RA (rauá¸ah al aá¹fal) teachersâ€™ character. Based on the dimension that seeks to understand the micro-subjective dimension that has dialectic relationship with the macro-subjective dimension , the paradigm used is Phenomenology. Ontologically, the paradigm understands that reality is complex and holistic. There are 16 pillars of Educators/Kindergarten Teachersâ€™ Character Builder, namely: affection, appreciation, space Provision for Self Development, trust, cooperation, mutual sharing, mutual motivation, mutual listening, positive mutual interaction, mutual moral value embedment, mutual sincere reminder, mutual enthusiasm giving, mutual self potential seeking, mutual teaching with humility, mutual inspiration, mutual respect for diversity.